2022
DOI: 10.3390/epigenomes6030029
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, Chromatin and Gene Organization of Toxoplasma gondii Subtelomeres

Abstract: Subtelomeres (ST) are chromosome regions that separate telomeres from euchromatin and play relevant roles in various biological processes of the cell. While their functions are conserved, ST structure and genetic compositions are unique to each species. This study aims to identify and characterize the subtelomeric regions of the 13 Toxoplasma gondii chromosomes of the Me49 strain. Here, STs were defined at chromosome ends based on poor gene density. The length of STs ranges from 8.1 to 232.4 kbp, with a gene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…5C and D ; Table S3 ). We also observed strong enrichment of TgBDP1 at the ends of chromosomes corresponding with regions of the telomeric repeats “TTTAGGG,” but TgBDP1 binding did not extend into subtelomeric regions as defined by Contreras et al ( 32 ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…5C and D ; Table S3 ). We also observed strong enrichment of TgBDP1 at the ends of chromosomes corresponding with regions of the telomeric repeats “TTTAGGG,” but TgBDP1 binding did not extend into subtelomeric regions as defined by Contreras et al ( 32 ).…”
Section: Resultssupporting
confidence: 56%
“…TgBDP1 also appears to be recruited to telomeric regions. Given that Toxoplasma telomeres are heterochromatic ( 32 , 51 ) and, therefore, the histones are hypoacetylated, it is unclear how TgBDP1 might be recruited to these regions. The extent of TgBDP1 enrichment at the telomeres may be artifactual due to the highly repetitive sequence structure of the telomeres that challenges accurate mapping of sequence reads, so further studies will be needed to confirm TgBDP1 binding to these regions.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TEs are enriched in these regions ( p < 0.001; t-test) while other repeats are not, indicating that TEs are the main contributor to repetitiveness in these regions. As low gene density is another hallmark of subtelomeres [ 70 ], we also tested gene content of S. mansoni ’s subtelomeres, and found that the mean fraction of nucleotides annotated as genes is statistically different between subtelomeres and chromosome bodies (t-test p < 0.01, Fig. 1 C) suggesting less density of genes in the former.…”
Section: Resultsmentioning
confidence: 99%
“…We realized that in T. gondii , N. caninum , and B. besnoiti , for which the available genome information includes the respective telomeric end, the LEA genes are subtelomeric, being located between 6.6 kb ( N. caninum ) up to 201 kb ( T. gondii ) upstream of the telomer ( Fig. 1A ) ( 65 ). Note that the annotated syntenies on ToxoDB (release 59) are not entirely correct ( Fig.…”
Section: Resultsmentioning
confidence: 99%